Research on Modern Corporate Cost Management and Cost Control Methods - Chang, Min (International Journal of Global Economics and Management, 2024)
With the continuous deepening of economic system reform and the advancement of economic structure transformation in China, the business environment for enterprises is becoming increasingly complex and competitive pressures are intensifying. In such a context, enterprises that wish to develop stably amidst fierce industry competition should actively adopt and implement modern corporate management concepts, enhancing the level of operational management comprehensively. Cost management, as a core component of modern enterprise management, is crucial not only for the economic benefits of a company but also directly relates to its market competitiveness. However, many companies still face numerous problems in cost management. To address these issues, modern enterprises must face the current situation and adopt effective measures. On the one hand, the importance of cost management should be emphasized through education to enhance everyone’s awareness of costs. On the other hand, the procedures for cost accounting must be standardized to ensure the accuracy and reliability of cost data. Moreover, it is essential to continuously explore and introduce advanced cost control methods to improve the effectiveness of cost control and cost management levels, thus providing a solid guarantee for the stable and healthy development of the company and meeting the needs of sustainable development in the future.